Research on the Forming of Mainstream Ideology Among College Students in the Era of “Short Video” - Liuyang Wang; Dingjun Yao (Studies in Social Science & Humanities, 2024)
Short videos, with their micro, fragmented, and diversified narrative methods, are profoundly changing the behavior and thinking patterns of users, and the mainstream ideological battlefield has been unprecedentedly impacted. The short video platform magnifies the characteristics of information dissemination in the Internet era. All users are both content publishers and content receivers, and the amount and speed of information dissemination are growing geometrically. Secondly, on the basis of producing a large number of short videos of the main theme, technological changes are utilized to fully improve the acceptance and interpretive power of the main theme ideology, providing a practical path for shaping the mainstream ideological identity of college students.